Relationship Between Substrate Concentration and Fermentation Product Ratios in Clostridium thermocellum Cultures - Brener, David (1984)
Growth of Clostridium thermocellum in batch cultures was studied over a broad range of cellobiose concentrations. Cultures displayed important differences in their substrate metabolism as determined by the end product yields. Bacterial growth was severely limited when the initial cellobiose concentration was 0.2 (wt/vol), was maximal at substrate concentrations between 0.5 and 2.0%, and did not occur at 5.0% cellobiose. Ethanol accumulated maximally (38.3 μmol/10(9) cells) in cultures with an initial cellobiose concentration of 0.8%, whereas cultures in 2.0% cellobiose accumulated only 17.3 μmol, and substrate-limited cultures (0.2% cellobiose) accumulated little, if any, ethanol beyond that initially detected (8.3 μmol/10(9) cells). In a medium with 0.8% cellobiose, ethanol was produced at a constant rate of approximately 1.1 μmol/10(9) cells per h from late-logarithmic phase (16 h) of growth well into stationary phase (44 h). When ethanol was added exogenously at levels more than twice the maximum produced by the cultures themselves (0.5% [vol/vol]), neither the extent of growth (maximum Klett units, 150) nor the amounts of ethanol produced (∼0.17%) by the culture was affected. The ratio of ethanol to acetate was highest (2.8) when cells were grown in 0.8% cellobiose and lowest (1.2) when cells were grown in 0.2% cellobiose.